Analyzing the Concept of Fairness in Polygamy through the Reference of Hadist Nabawi - Abdul Rahman Ramadhan (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
This research aims to analyze and understand the meaning and significance of the concept of " fairness" in the practice of polygamy based on the Prophet's hadith. Polygamy is a complex and controversial issue in contemporary society. The husband's unfair attitude towards his wife and children is often the cause of complicated problems in the practice of polygamy in Indonesia. The forms of husband's unfairness in polygamous marriages also vary, including in matters of food, clothing, shelter and division of days. Husband's unfairness is almost always a finding in research that discusses the problems and negative impacts of polygamous marriages in Indonesia. The results show that the concept of fairness in the practice of polygamy referred to in the traditions of the Prophet shallallahu 'alaihi wa sallam and the explanations of the scholars include: (1) Fairness in the division of nights, overnight stays (qasm) and visits, although doing the division of nights the Prophet also gathered his wives at night and visited all of his wives during the day; (2) Fairness in providing maintenance which includes clothing, shelter and food; (3) Fairness in determining which wife to bring to accompany him on long trips by drawing lots; and (4) There is no obligation to be fair in matters of love and intercourse. This research is expected to provide a better understanding of the practice of polygamy in Islam and the concept of fairness applied.